THE ANALYSIS OF SHORT STORY’S FIGURATIVE LANGUAGE DARING THE COVID-19 PANDEMIC OUT BREAK : THE CASE OF INDONESIA SECONDARY SCHOOL - Ramadana, Sonya; Dian Arief Pradana; St. Shabibatul Rohmah (LUNAR, 2024)
This study aims to determine and describe the figurative language used in short stories. The research data were in the form of speech in text extracts, and were collected through document analysis using descriptive qualitative methods. The data were selected purposively. Data are selected using a coding system to identify data using figurative language. The selected data were analyzed using several Hymes communication ethnographic components which separate language form and language meaning. Figurative language is classified into types of figures based on the Kennedy theory. there are ten types of figurative language, namely: Metaphor, Simile, Personification, Pleonasm, Hyperbola, Repetition, Rhetoric, Ellipsis. The results of this study are expected to provide information about various figurative languages ​​and messages. behind it and knowing how figurative language is used in literary works, especially in short stories for students. In addition, it is also hoped that it can be useful for English language lecturers as input and consideration for applying some material about types of figurative language, especially those used in short stories. Other researchers can use the findings of this study as a reference for conducting further research on similar issues.